Evolution of rDNA FISH patterns in the Fagaceae - Ribeiro, Teresa; Loureiro, João; Santos, Conceição; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2011)
The Fagaceae is one of the most important plant families in European forest ecosystems, and it includes several genera distributed in the Northern hemisphere. In this work we studied the genome organization and evolution within the family, by karyotyping and physically mapping rDNA in ten European and Asian species of the genera Fagus, Quercus, and Castanea. All of the species studied had a chromosome number of 2n=2x=24, except for the first report of a single individual of Quercus suber which proved to be triploid (2n=3x=36). The rDNA physical mapping revealed several patterns: the dominant one is present in European and Asian Quercus subgenus Quercus, and in Castanea sativa and Castanea crenata, consisting of two 18S–25S rDNA loci (one subterminal major and one pericentromeric minor) and one 5S rDNA pericentromeric locus. In Fagus sylvatica and in Quercus sessilifolia, different patterns were observed: four terminal 18S–25S rDNA loci and two 5S rDNA pericentromeric loci in the former, and five 18S–25S rDNA loci (three terminal and two intercalary) and one 5S rDNA pericentromeric locus in the latter. In Castanea mollissima a distinct rDNA distribution pattern with two intercalary 18S–25S rDNA loci and two 5S rDNA was found. These findings suggest rDNA loci restructuring during Castanea evolution, and variability of 18S–25S loci between Quercus and Cyclobalanopsis subgenera.
Keywords: Castanea; fagaceae karyotype; Fagus; Quercus; rDNA; triploid quercus suber

Determination of genetic stability in long-term somatic embryogenic cultures and derived plantlets of cork oak using microsatellite markers - Lopes, Tina; Pinto, Glória; Loureiro, João; Costa, Armando; Santos, Conceição (Tree Physiology, 2006)
Microsatellites were used to test genetic stability in somatic embryos (SE) of Quercus suber L. The SE were obtained by a simple somatic embryogenesis protocol: leaf explants from two adult plants (QsG0, QsG5) and from two juvenile plants (QsGM1, QsGM2) were inoculated on Murashige and Skoog (MS) medium with 2,4-dichlorophenoxyacetic acid and zeatin. Calluses with primary embryogenic structures were transferred to MSWH (MS medium without growth regulators) and SE proliferated by secondary somatic embryogenesis. High morphological heterogeneity was found among cotyledonary SE. However, converted plants looked morphologically normal with well-developed rooting systems and shoots. The genetic stability of the plant material during the somatic embryogenesis process was evaluated by using six to eight nuclear microsatellites transferred from Q. myrsinifolia Blume, Q. petraea (Matts.) Liebl. and Q. robur L. Five of eight microsatellites distinguished among the genotypes analyzed, and for QsG0, QsGM1 and QsGM2, uniform microsatellite patterns were generally observed within and between SE and the respective donor genotypes. For genotype QsG5, the same pattern was observed in all samples analyzed except one, where the mutation percentage was 2.5%. We conclude that microsatellite markers can be used to assess genetic stability of clonal materials and to determine genetic stability throughout the process of somatic embryogenesis. The simple somatic embryogenesis protocol described has potential for the commercial propagation of Q. suber because it results in a low percentage of mutations.
10.1093/treephys/26.9.114510.1093/treephys/26.9.1145
Keywords: Genetic variability; Quercus suber; Somatic embryogenesis; SSR markers